2011
DOI: 10.1088/1748-9326/6/4/045101
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a giant wind farm on precipitation in a regional climate model

Abstract: The Weather Research and Forecasting (WRF) model is employed as a nested regional climate model to study the effect of a giant wind farm on warm-season precipitation in the eastern two-thirds of the USA. The boundary conditions for WRF are supplied by 62 years of NCEP/NCAR (National Center for Environmental Prediction/National Center for Atmospheric Research) global reanalysis. In the model, the presence of a mid-west wind farm, either giant or small, can have an enormous impact on the weather and the amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 20 publications
0
54
0
Order By: Relevance
“…In the latter approach, turbulence can be explicitly added by the parameterization [e.g., Fitch et al, 2012], or implicitly generated through the creation of shear within the rotor layer [e.g., Jacobson and Archer, 2012]. These wind-farm models have been used to simulate wake impacts on local hydrometeorology [Baidya Roy, 2011;Fitch et al, 2013a], investigate the aggregate effect of wind power on regional and global climate [Kirk-Davidoff and Keith, 2008;Fiedler and Bukovsky, 2011;Wang and Prinn, 2011;Vautard et al, 2014;Fitch, 2015a], evaluate the sensitivity of wind-farm output to surface characteristics [Vanderwende and Lundquist, 2015], and estimate global wind resources [Lu et al, 2009;Marvel et al, 2013;Jacobson and Archer, 2012;Adams and Keith, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter approach, turbulence can be explicitly added by the parameterization [e.g., Fitch et al, 2012], or implicitly generated through the creation of shear within the rotor layer [e.g., Jacobson and Archer, 2012]. These wind-farm models have been used to simulate wake impacts on local hydrometeorology [Baidya Roy, 2011;Fitch et al, 2013a], investigate the aggregate effect of wind power on regional and global climate [Kirk-Davidoff and Keith, 2008;Fiedler and Bukovsky, 2011;Wang and Prinn, 2011;Vautard et al, 2014;Fitch, 2015a], evaluate the sensitivity of wind-farm output to surface characteristics [Vanderwende and Lundquist, 2015], and estimate global wind resources [Lu et al, 2009;Marvel et al, 2013;Jacobson and Archer, 2012;Adams and Keith, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbines could modify the surface-atmosphere exchanges by increasing surface roughness [8][9][10], changing the stability of atmospheric boundary layer (ABL) [11], enhancing turbulence in the rotor wakes [12,13], and interrupting the low-level-jet in stable ABL [14]. A few studies show that the large-scale deployment of wind farms alters the local temperature by up to a few degrees [10,13,[15][16][17], reduces precipitation by up to 20% [18], and even mitigates extreme weather [19]. These studies are basically based on limited observation analysis [13,16,20] or model simulations [12,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous modelling investigations suggested that hypothetical gigantic wind farms, installed over one or several continents, would modify the regional climate and mean atmospheric circulation [17][18][19] , with temperature changes reaching B1°C and regional precipitation changes exceeding 10% (ref. 19).…”
mentioning
confidence: 99%
“…Additional TKE is calculated as the difference between the energy extracted from the flow and the electrical power produced 11 . It avoids the overestimation of local temperature changes such as that found using a roughness-based approach 18 . This parameterization is implemented in the Weather Research and Forecast (WRF) model 21,22 (see Methods for more details and information on the WRF model configuration used here).…”
mentioning
confidence: 99%